Enterococcus faecalis Clones in Poultry and in Humans with Urinary Tract Infections, Vietnam - Louise Ladefoged Poulsen (Emerging Infectious Diseases, 2012)
Enterococcus spp. as pathogens have increased, but the sources of infection often remain unclear. To investigate whether poultry might be a reservoir for E. faecalis–associated urinary tract infections (UTIs) in humans, we characterized E. faecalis isolates from patients in Vietnam with UTIs during January 2008–January 2010 and poultry living in close contact with them by multilocus sequence typing (MLST), pulsed-field gel electrophoresis, analysis of antimicrobial drug susceptibility patterns, and sequencing of virulence genes. In 7 (23%) of 31 UTI cases, we detected identical MLST, indistinguishable or closely related pulsed-field gel electrophoresis patterns, and similar antimicrobial drug susceptibility patterns. Isolates from urine and poultry showed identical virulence gene profiles, except for 1 variation, and individual genes showed identical sequences. The homology of isolates from urine and poultry further indicates the zoonotic potential and global spread of E. faecalis sequence type 16, which recently was reported in humans with endocarditis and in pigs in Denmark.